META ANALISIS: IMPLEMENTASI STRATEGI DIRECTED READING THINKING ACTIVITY (DRTA) DALAM MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN - Najva, Madhuma Acharee Nazhelya; Sarifah, Iva; Yudha, Chrisnaji Banindra (Universitas Negeri Medan, 2024)
The reading comprehension ability of elementary school students in Indonesia is very low due to a lack of motivation in reading which will have a negative impact on students' academic and daily development. An effort to overcome this is by implementing an appropriate learning strategy, namely the Directed Reading Thinking Activity (DRTA) strategy which can improve students' reading comprehension skills. The method used in this research is a literature review with meta analysis techniques which aims to re-analyze articles regarding the implementation of the Directed Reading Thinking Activity (DRTA) strategy in elementary schools. The population of this research is relevant articles from journals indexed by Scopus and Google Scholar with a sample of 20 articles taken using purposive sampling techniques. The results of this research obtained Sig. (2-tailed) is 0.000 <0.05 and the t value exceeds t table (7.386 > 2.093), with the conclusion that Ho is rejected and Ha is accepted which shows that the application of the Directed Reading Thinking Activity (DRTA) strategy has proven to be effective in improving students' reading comprehension skills.